2016
DOI: 10.1542/peds.2015-2493
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year BMI Outcomes From a School-Based Intervention for Nutrition and Exercise: A Randomized Trial

Abstract: OBJECTIVES: This study examined the long-term effects on BMI of a randomized controlled trial of Students for Nutrition and Exercise, a 5-week, middle school-based obesity prevention intervention combining school-wide environmental changes, encouragement to eat healthy school cafeteria foods, and peer-led education and marketing. METHODS:We randomly selected schools from the Los Angeles Unified School District and assigned 5 to the intervention group and 5 to a wait-list control group. Of the 4022 seventhgrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 21 publications
1
59
0
3
Order By: Relevance
“…Improvements were not identified in odds of overweight/obesity (n = 2; 1.04 (0.91, 1.19)) [ 44 , 66 ], overweight (n = 1; 1.03 (0.94, 1.12)) [ 74 ], or obesity (n = 2; 1.25 (1.07, 1.46)) [ 66 , 74 ]; BMI (n = 3; 0.19 kg/m 2 (-0.12, 0.50)) [ 44 , 66 , 67 ]; or BMI z-score (n = 2; 0.01 (-0.04, 0.05)) [ 44 , 66 ]. Another 3 studies [ 43 , 55 , 60 ] focusing on water provision reported improvements in BMI z-score [ 60 ], prevalence of overweight/obesity [ 60 ] and odds of overweight [ 55 ], while obesity prevalence [ 60 ] and BMI percentile were unchanged [ 43 ]. Only 1 study [ 67 ] evaluated metabolic risk factors, finding significant decreases in total cholesterol, LDL cholesterol, and triglycerides, and blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Improvements were not identified in odds of overweight/obesity (n = 2; 1.04 (0.91, 1.19)) [ 44 , 66 ], overweight (n = 1; 1.03 (0.94, 1.12)) [ 74 ], or obesity (n = 2; 1.25 (1.07, 1.46)) [ 66 , 74 ]; BMI (n = 3; 0.19 kg/m 2 (-0.12, 0.50)) [ 44 , 66 , 67 ]; or BMI z-score (n = 2; 0.01 (-0.04, 0.05)) [ 44 , 66 ]. Another 3 studies [ 43 , 55 , 60 ] focusing on water provision reported improvements in BMI z-score [ 60 ], prevalence of overweight/obesity [ 60 ] and odds of overweight [ 55 ], while obesity prevalence [ 60 ] and BMI percentile were unchanged [ 43 ]. Only 1 study [ 67 ] evaluated metabolic risk factors, finding significant decreases in total cholesterol, LDL cholesterol, and triglycerides, and blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of that review interpreted these interventions as having been conducted over limited time periods and primarily promoted lifestyle changes that may eventually result in healthier BMI levels in the long‐term (Quelly, Norris, & DiPietro, ). In fact, the previous trial with school‐based intervention expected significantly lower body weight among obese students after two years (Bogart et al, ). Thus, long‐term follow‐ups should be considered for future studies when designing mobile phone interventions, with a target on physical fitness‐related outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…30,31 For the present analysis, we analyzed data from student-parent dyads who were surveyed pre-intervention. Students were drawn from seventh-grade classes from nine LAUSD schools with >50% National School Lunch Program (NSLP) eligibility, a proxy for low income.…”
Section: Methodsmentioning
confidence: 99%